Libertà religiosa e riforma (incompiuta) dell’ordinamento penitenziario (Stato, Chiese e pluralismo confessionale, 2023)
Religious freedom and reform (unfinished) of the penitentiary systemABSTRACT: The article analyzes the possible alliance between religion and the re-educational finality of criminal sanctions in the actions of application of the art. 27, par. 3, of the Italian Constitution. The reflection also realizes a reconstruction of the legal discipline of religious freedom in the penitentiary system also with reference to the relationship with the security needs present in detention institutions. The final part is dedicated to the incomplete reform of the Italian penitentiary system in the part relating to religious freedom.SOMMARIO: 1. L’alleanza tra religione e finalità rieducativa delle pene nelle dinamiche di attuazione dell’art. 27 (terzo comma) della Costituzione - 2. La libertà religiosa nell’ordinamento penitenziario - 3. Esigenze di sicurezza e previsione di limiti ulteriori all’esercizio della libertà religiosa negli istituti penitenziari - 4. L’incompiuta riforma dell’ordinamento penitenziario nella parte relativa alla libertà religiosa.